Pengaruh Kompetensi, Partisipasi Penganggaran, Pemanfaatan Teknologi Informasi Terhadap Akuntabilitas Dana Desa Kabupaten Kepulauan Meranti - Ranti Novera; Abrar Abrar; Dian Saputra (Akuntansi & Ekonomika, 2022)
This research aims to determine the influence of Human Resource Competencies, Budgeting Participation and Utilization of Information Technology on Village Fund Management Accountability in Meranti Islands Regency.This research is a type of quantitative research. The population in this study was 96 villages and the total sample was 32 villages with 128 respondents. Respondents consisted of the Village Head, Village Secretary, Village Treasurer and Government Kasi. The research data was collected through questionnaires and the sampling technique used was a purposive sampling technique. The data analysis used is Multiple Linear Regression Analysis using the help of the SPSS 25 program. The results of the research data concluded that Human Resource Competence, Budgeting Participation and Untilization of Information Technology had a positive and significant effect on the Accountability of Village Fund Management in the Meranti Islands Regency.